KONTRIBUSI TENAGA KERJA “BORONG PRESTASI” PADA PENANGANAN PASCA PANEN KAYU JATI TERHADAP PENDAPATAN KELUARGA (Studi Kasus di TPK Randublatung III Kecamatan Randublatung Kabupaten Blora) - Gadhis Mabruri; Dewi Hastuti; Renan Subantoro (MEDIAGRO, 2018)
The aims of research is to find out the outpouring of hours of labor, the contribution of labor “Borong Prestasi” (TKBP) to the family income and factors affecting labor “Borong Prestasi” income. The basic method used is descriptive method. Respondents are took in stratified random sampling with the number of respondents as many as 52 people. The data used are primary and secondary data. Data collected by interview, observation and recording. Based on analysis of data on average hours TKBP is 5,2 hours per day. TKBP contribution to the family income is 40 percent of TKBP income amounted Rp 595.942 to total family income amounted Rp 1.486.519. R2values were obtained using multiple linier regression model for 0,957 means that the independent variable the number of jati wood obtained, the outpouring of hours of labor, length of work and age affecting to TKBP income in post-harvest handling jati wood is 95,7 percent, while 4,3 percent is influenced by other variables outside the model. F test result showed that the number of jati wood obtained, the outpouring of hours of labor, length of work and age together are very significant for TKBP income. T test result showed that the variable of the number of jati wood obtained significant and the outpouring of hours of labor significantly effect for TKBP income, while the variable length of work and age is not significant on TKBP income.Keywords: contribution, jati wood, labor “Borong Prestasi”, Blora Regency